COMPOSITE MATERIALS based on exfoliated vermiculite for electromagnetic radiation shieldS - M. A. Dmitriev; S. N. Petrov; T. A. Pulko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of the study composite materials for electromagnetic radiation shields based on exfoliated vermiculite are described. Shielding characteristics of formed designs based on composite materials in the frequency range 0,7…17 HHz are obtained.